1988
DOI: 10.3354/dao005205
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of protozoan pathogen Perkinsus marinus infections in American oysters Crassostrea virginica exposed to the chemical carcinogen n-nitrosodiethylamine (DENA)

Abstract: American oysters Crassostrea virginica exposed to high concentrations (600 mg I-') of nnitrosodiethylamine (DENA) during winter (February to May) showed significant enhancement of an epizootic apicomplexan parasite, Perkinsus rnarinus. The parasite reproduced and caused atypical lesions in exposed oysters in water temperatures at its lower range (20°C). The reasons for this enhancement are not clear but may reflect damage to the oysters' nonspecific, cellular defense mechanisms by the DENA without concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Environmental stress, such as pollutants, may affect the physiology of the host organism, thus negatively affecting a host response to disease-causing agents or restricting available habitat within the host for parasitic agents (Laird 1961, Lauckner 1983, Cheng 1988, Winstead & Couch 1988. Parasites themselves can also be affected by environmental extremes.…”
Section: Parasitism In Seep and Vent Musselsmentioning
confidence: 99%
“…Environmental stress, such as pollutants, may affect the physiology of the host organism, thus negatively affecting a host response to disease-causing agents or restricting available habitat within the host for parasitic agents (Laird 1961, Lauckner 1983, Cheng 1988, Winstead & Couch 1988. Parasites themselves can also be affected by environmental extremes.…”
Section: Parasitism In Seep and Vent Musselsmentioning
confidence: 99%
“…Laboratory exposure to contaminants can significantly alter immunity in invertebrates from diverse phyla, including annelids (Suzuki et al 1995, Ville et al 1995, molluscs (Coles et al 1994, Auffret & Oubella 1997, Cima et al 1998), crustaceans (Smith & Johnston 1992, Smith et al 1995 and ascidians , Cima et al 1997, Raftos & Hutchinson 1997. Under laboratory conditions, contaminant-induced immunomodulation can lead to increased susceptibility of molluscs to disease (Winstead & Couch 1988, Chu & Hale 1994, Fisher et al 1999.Crude oil comprises a mixture of 1000s of components, including polycyclic aromatic hydrocarbons (PAH). Low molecular mass PAHs are among the most acutely toxic components, while some of the high molecular mass PAHs are potent carcinogens.…”
mentioning
confidence: 99%
“…The lack of parasites in anemones at the 200E station in June 1983 may indicate that those anemones with parasites had already died within the month following the discharge, either because they were m.ore susceptible to increased sedimentation and chemical stress or because the intensity of the parasite infections had increased when the anemones' normal mechanisms of resistance were weakened. Other studies have suggested that parasite-compromised hosts are more vulnerable to pollutants (Sindermann 1983, Yevich & Barszcz 1983), although Couch & Courtney (1977) and Winstead & Couch (1988) reported enhanced viral and protozoan infections in shrimp and oysters, respectively, when exposed to certain toxic chemicals. In the latter situations, the cause of death could not be attributed to chemical exposure alone.…”
Section: Discussionmentioning
confidence: 95%